Synthesis and microstructure studies of nano-sized cerium-zinc phosphates - Hanna, Adly Abdella; Mousa, Sahar Mohamed; Sherief, Marwa Adel; Elkomy, Gehan Mahmoud (European Journal of Chemistry, 2011)
A system of Ce(SO4)2.4H2O, Zn(CH3COO)2.2H2O and phosphoric acid was studied by the chemical reaction between the precursor materials. The cerium cations were replaced by zinc cations (x) in the range of x = 0.0-1.0. The obtained gels were dried and calcinated at 650 oC for 2 hrs. The effect of calcination on the produced phases was studied using X-ray diffraction (XRD) and infrared spectroscopy (IR). The thermal behaviors of only the dried samples were investigated employing differential scanning calorimetric (DSC) and thermogravimetric analysis (TGA). The transmission electron microscope (TEM) was used to investigate the morphology, crystallinity and particle size of both dried and calcined samples. The TEM results indicated that the crystallinity was improved by increasing the zinc contents. The importance of Zn, Ce phosphates return to their using as UV-shielding agents.